Survey of Research on Mathematical Solutions of Programming Problems - Orden, Alex (Management Science, 1955)
My topic in this panel discussion on management science today is the status of research on mathematical solution of programming problems. The word “programming” refers here to optimal allocation, as in machine loading, or to optimal scheduling of one kind or another. “Optimal allocation” may be taken as referring to static problems, while “optimal scheduling” refers to dynamic problems, varying over time. The static and dynamic problems are, at the present stage of management science development, generally speaking, studied by means of the same techniques.